SERVANT LEADERSHIP DAN KINERJA ORGANISASI STUDY SISTEMATIK LITERATUR REVIEW - Arief Prayitno; Rusdin Tahir (AdBispreneur : Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2022)
Research on servant leadership is interesting to study, because it involves virtue, ethics, morals and ideal leadership. The results of the discussion of scientists gave birth to the type of leadership in organizational theory that developed. Scholars debate the theory of servant leadership in an organizational context. The main concern is considered suitable, worthy, and valuable for organizational success, because the characteristics of servant leadership focus on listening, empathy, healing, awareness, persuasion, conceptualization, foresight, openness, commitment to growth, and building community, which are prerequisites for organizational progress and success. . The purpose of this study is to identify servant leadership theory based on empirical studies, involving population and sample sizes, the results of which show its influence on organizational goals. The analysis method uses a Systematic Literature Review (SLR) to assess how it works, its implementation and its influence on organizational dynamics and performance. The process of skinning from the population to the end of 35 studies in empirical studies revealed servant leadership theory: generally accepted in the organizational context; able to improve organizational performance; not suitable to be practiced in certain fields; and can contribute to organizational goals and shared success. This study contributes to the methodology of the SLR approach to organization and leadership, highlighting and mapping the influence and workings of servant leadership by looking at new research topics.Penelitian tentang servant leadership menarik dikaji, karena menyangkut pada kebajikan, etika, moral dan kepemimpinan ideal. Hasil diskusi ilmuan melahirkan tipe kepemimpinan dalam teori organisasi yang berkembang. Para ilmuan memperdebatkan teori servant leadership dalam konteks organisasi. Perhatian utama dinilai cocok, layak, dan berharga untuk kesuksesan organisasi, karena karakteristik dari servant leadership fokus pada mendengarkan, empati, penyembuhan, kesadaran, persuasi, konseptualisasi, kejelian, keterbukaan, komitmen untuk pertumbuhan, dan membangun komunitas, menjadi syarat kemajuan dan kesuksesan organisasi. Tujuan penelitian ini mengidentifikasi teori servant leadership berdasarkan studi empiris, melibatkan ukuran populasi dan sampel, hasil yang menunjukkan pengaruhnya terhadap tujuan organisasi. Metode analisis menggunakan Systematic Literature Review (SLR) guna menilai cara kerja, penerapan dan pengaruhnya terhadap dinamika dan kinerja organisasi. Proses skinning dari populasi sampai akhir dari 35 penelitian pada studi empiris diungkapkan teori servant leadership: berlaku umum dalam konteks organisasi,  mampu meningkatkan kinerja organisasi, tidak cocok dipraktikan pada bidang tertentu, dan dapat membantu tujuan organisasi dan kesuksesan bersama. Studi ini berkontribusi pada metodologi dengan pendekatan SLR bidang organisasi dan kepemimpinan, menyoroti dan memetakan pengaruh dan cara kerja servant leadership dengan melihat topik penelitian baru.